Akibat Hukum Notaris Yang Bekerjasama Dengan Virtual Office - Novita Agatharia Tampubolon (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
The Notary profession is seen as an honorable profession because it has a major role in providing legal services to the public. In carrying out their duties and responsibilities, a Notary is required to not only master the juridical aspects, but also have full awareness of the moral and ethical values attached to their position. In current notarial practice, technological developments and demands for efficiency have encouraged some Notaries to establish cooperation with virtual office service providers, which causes Notaries to be able to list a certain address as office domicile, even though factually they do not carry out office activities directly in that place. Based on this, this research aims to find out the legal consequences for Notaries who cooperate with virtual offices. This research is a type of normative juridical research analyzed using statutory and conceptual approaches. The results of this study indicate that the legal consequences arising from the cooperation between Notary and virtual office are potential formal defects in the authentic deed made, legality and legitimacy of Notary, and potential violations in administrative, criminal, and civil fields.